Proceedings of the 2021 CHI Conference on Human Factors in Computing Systems 2021
DOI: 10.1145/3411764.3445372
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Multiple Parallel Phrase Suggestions on Email Input and Composition Behaviour of Native and Non-Native English Writers

Abstract: We present an in-depth analysis of the impact of multi-word suggestion choices from a neural language model on user behaviour regarding input and text composition in email writing. Our study for the first time compares different numbers of parallel suggestions, and use by native and non-native English writers, to explore a trade-off of "efficiency vs ideation", emerging from recent literature.We built a text editor prototype with a neural language model (GPT-2), refined in a prestudy with 30 people. In an onli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 69 publications
1
45
0
Order By: Relevance
“…Who will own the authorship of the model-generated content and how could the shifting responsibilities and ownership of the consent be misused [Weiner 2018] (see §5.5: economics for a more in-depth discussion)? What are the long-term implications that foundation models will have on our work, language and culture [Hancock et al 2020;Buschek et al 2021]? Of particular relevance to this last question is the fact that foundation models are trained on observed data and do not necessarily inform us about causality.…”
Section: Impact On End-user Interaction With Ai-infused Applicationsmentioning
confidence: 99%
“…Who will own the authorship of the model-generated content and how could the shifting responsibilities and ownership of the consent be misused [Weiner 2018] (see §5.5: economics for a more in-depth discussion)? What are the long-term implications that foundation models will have on our work, language and culture [Hancock et al 2020;Buschek et al 2021]? Of particular relevance to this last question is the fact that foundation models are trained on observed data and do not necessarily inform us about causality.…”
Section: Impact On End-user Interaction With Ai-infused Applicationsmentioning
confidence: 99%
“…Additionally, in a study by Robertson et al [92], the authors found that instead of accepting an AI-generated text suggestion by clicking on it, one participant chose to write out the same words themselves, expressing that they desired more agency when writing messages. Buschek et al [18] also demonstrated that the more AI-generated text suggestions a person accepted in their emails, the lower they perceived their authorship over the message to be. Both of these insights emphasize the action initiation dimension of agency; participants were seemingly interested in feeling like they were the ones who generated the text in their messages, as opposed to the AI system.…”
Section: Human and Machine Agencymentioning
confidence: 99%
“…For instance, Todi et al (2021) showed that approaches based on reinforcement learning can be used to automatically adapt related user interfaces. For interactive NLP, Buschek et al (2021) investigated how different numbers of phrase suggestions from a neural language model impact user behavior while writing, collecting a dataset of 156 people's interactions. In the future, data such as this might be used, for example, to train a model that replicates users' selection strategies for text suggestions from an NLP system.…”
Section: Employing User Models As Proxies For Interactive Evaluationsmentioning
confidence: 99%